Phenotypic Resistance of (MRSA) Clinical Isolates to Some Macrolide Antibiotic Groups - Ali Yaseen; Jaleel Samanje; Qahtan Adnan Rasheed; Rafah Sabah Barrak; Afraa Brahim (Journal of Techniques)
Antimicrobial resistance is one of the most significant global threats to human health in recent times, and it limits the achievement of several of the sustainable development goals. Methicillin-resistant Staphylococcus aureus (MRSA) is among the most essential multidrug-resistant bacterial pathogens. The study aimed to determine the prevalence of (MRSA) from different clinical samples to emphasise the suitable treatment. One hundred fifty different clinical samples were collected. All these samples were subjected to classical microbiological testing, which included culturing directly on mannitol salt agar and antibiotic susceptibility test (A.S.T). The results observed that only 32 out of 150 samples of MRSA isolates were identified using cefoxitin 30 (µg) as a screening antibiotic, as suggested by CLSI. These 32 MRSA isolates showed resistance toward penicillin and cefoxitin, high sensitivity against vancomycin, and moderate resistance against doxycycline and azithromycin. Considering the phenotyping resistance toward macrolide antibiotic groups, 10/32 (31.25%) showed S-phenotype,18/32 (52.65%) showed R-phenotype,4/32 (12.5%) showed D-phenotype while no MRSA isolated showed D+ phenotype. This study concludes that inducible clindamycin resistance of S. aureus (MRSA) increases the difficulty of treating S. aureus bacterial infections.